Sailor's Hope: The Life and Times of William Cooper, Agrarian Radical in an Age of Revolutions - Sweeny, Robert C. H. (Labour / Le Travail, 2012)
The article reviews the book "Sailor's Hope: The Life and Times of William Cooper, Agrarian Radical in an Age of Revolutions," by Rusty Bittermann.
Keywords: BITTERMAN; Rusty; BOOKS – Reviews; COOPER; William; Nonfiction; SAILOR'S Hope: The Life & Times of William Cooper; Agrarian Radical in an Age of Revolutions (Book)

Bibliography: Recent Publications in Canadian Labour History - Lonardo, Michael; Sweeny, Robert C. H. (Labour / Le Travail, 2008)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]
Keywords: BIBLIOGRAPHY (Documentation); History; Labor

Bibliography: Recent Publications in Canadian Labour History [58, Fall 2006] - Lonardo, Michael; Sweeny, Robert C. H. (Labour / Le Travail, 2006)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]
Keywords: BIBLIOGRAPHY (Documentation); WOMEN & war